PENGUATAN KARAKTER PELAJAR PANCASILA MELALUI KEGIATAN PESANTREN RAMADHAN (STUDI DI SD ISLAM PLUS SALSABILA AL IKHSAN MAGELANG - Hozaimi (ABDAU : Jurnal Pendidikan Madrasah Ibtidaiyah, 2022)
This study aims to describe strengthening the character (profile) of Pancasila students through the activities of the Ramadhan Islamic Boarding School. The research was conducted at SD Islam Plus Salsabila Al Ikhsan Magelang in the month of Ramadan to Shawwal in 1443 Hijriyah, coinciding with April to May of 2022 AD. The method used in this research is observation, documentation review, and interviews. The results of the analysis show that the character (profile) of the Pancasila students consists of firstly believing, fearing God Almighty, and having noble character, second with global diversity, third working together, fourth independent, fifth critically reasoning, and sixth creative. As for what was found in a series of events at the Ramadhan Islamic Boarding School at SD Islam Plus Salsabila Al Ikhsan Magelang consisting of the first Bhakti Mosque Safari, the second Learning to Read and Memorizing the Qur'an, the third Thematic was fun, Fourth sharing Blessings, the fifth night of Faith and Piety (MABIT) , the sixth Adhan Practice, the seventh Speech/Lecture Practice, the eighth Creativity (Life Skill), and the ninth Halal bi Halal. This shows that the strengthening of the character (profile) of Pancasila students can be done through the activities of the Ramadhan Islamic Boarding School.